Impact of low-protein diets on broiler nutrition, production sustainability, gene expression, meat quality and greenhouse gas emissions - Ahmad Salahi; M.H. Shahir; Youssef A. Attia; Khaled Nasr El-din Fahmy; Fulvia Bovera; Vincenzo Tufarelli (Journal of Applied Animal Research)
This review explores the effects of low-crude protein diets (LCPD) on broiler chicken production, focusing on sustainability, gene expression, meat quality and environmental impacts. LCPD supplemented with amino acids, enzymes, and probiotics has been shown to influence protein utilization efficiency, meat quality, environmental pollution, and bird welfare. However, gaps exist in the understanding of the relationship between LCPD and immunity, footpad lesions, gut microbiota, economic aspects, and amino acid sparing. LCPD and plant-based protein sources significantly reduced C. perfringens in ileum and cecum, while increasing the abundance Lactobacillaceae. Amino acid digestibility increased in ileum and jejunum with LCPD, and fortification with specific amino acids, while maintaining the non-essential to essential amino acid ratio (NEAAs/ EAAs) at 47:53, resulted in optimal performance. In addition, the reduction of CP to 15% decreased tibia length, calcium retention, and bone mass accumulation. Additionally, 20% excessive total amino acids (TAAs) significantly reduced tibial mineralization. Further research is needed to optimize LCPD formulations and address potential barriers to their implementation in the poultry industry. The available literature emphasizes the effects of LCPD supplemented with amino acids, enzymes, and probiotics.. on broiler performance, protein utilization efficiency, meat quality, environmental pollution, green gas emissions, health, and bird welfare.